Outdoor Physical Activity During the First Wave of the COVID-19 Pandemic. A Comparative Analysis of Government Restrictions in Italy, France, and Germany - Michelini, Enrico; Bortoletto, Nico; Porrovecchio, Alessandro (Frontiers in Public Health, 2021)
Introduction: Mandated restrictions on outdoor physical activity (PA) during the coronavirus pandemic disrupted the lifeworld of millions of people and led to a contradictory situation. On the one hand, PA was perceived as risky behaviour, as it might facilitate transmission of the virus. On the other hand, while taking precautions, regular PA was an important tool to promote the population's health during the lockdown. Methods: This paper examines the differences in government restrictions on PA in France, Germany, and Italy during the first wave of the COVID-19 pandemic. We draw on techniques of qualitative content analysis and apply a critical theoretical framework to assess the countries' restrictions on PA. Results: Our analysis shows that the restrictions on PA varied in the three countries, in all three countries. This variance is attributed both to differences in the timing and severity of the pandemic in the countries analysed, as well as to the divergence in the relationships between the countries' sport and health systems. Conclusion: At the national level, the variance in restrictions on PA reflect the differences in the spread of the coronavirus and in the health systems' understanding of and approach to PA. The global scientific discourse on the pandemic represents a further key influencing factor. The management of the coronavirus pandemic has demonstrated that the extreme complexity of societies in terms of public health, politics, and the economy pose challenges and unsolvable contradictions.